Utilisation Of Standardized Uptake Value Maximum (SUVMAX) In Single Photon Emission Computed Tomography / Computed Tomography (SPECT/CT) To Differentiate Between Metastatic Vs Degenerative Joint Disease Of The Spine In Bone Scan For Prostate Cancer Patients - Rohani, Mohd Fazrin Mohd (2019)
Objective. Qualitative interpretation in bone scan is often complicated by the presence of degenerative joint disease (DJD) especially in the elderly patient. The aim of this study is to compare objectively 99mTc-MDP tracer uptake between DJD and osseous metastases of the spine using semi-quantitative assessment with SPECT SUV. Subjects and Methods. Bone scan with SPECT/CT using 99mTc-MDP were performed in 34 patients diagnosed with prostate carcinoma. SPECT/CT were performed based on our institutional standard guidelines. SUVmax based on body weight in 238 normal vertebrae visualized on SPECT/CT were quantified as baseline. A total of 211 lesions in the spine were identified on bone scan. Lesions were characterized into DJD or bone metastases based on its morphology on low dose CT. Semi-quantitative evaluation using SUVmax were then performed on 89 DJD and 122 metastatic bone lesions. Results. The mean SUVmax for normal vertebrae was 7.08 ± 1.97, 12.59 ± 9.01 for DJD and 36.64 ± 24.84 for bone metastases. The SUVmax of bone metastases were significantly greater than DJD (p value <0.05). To assess for diagnostic accuracy, receiver operating characteristic (ROC) curve was performed. The area under the curve (AUC) was found to be fairly high at 0.874 (95% CI: 0.826-0.921). The cut-off SUVmax value ≥ 20 gave a sensitivity of 73.8% and specificity of 85.4% in differentiating bone metastases from DJD. Conclusion. SPECT SUVmax was significantly higher in bone metastases than DJD. Semi-quantitative assessment with SUVmax can complement qualitative analysis. A cutoff SUVmax of ≥ 20 can be used to differentiate bone metastases from DJD. However, it is not feasible to be applied clinically due to the considerable overlap of SUVmax between DJD and bone metastases.